Modulation of Microstructure and Charge Transport in Polymer Monolayer Transistors by Solution Aging. Issue 11 (6th September 2021) - Lin, Xuemei; Liu, Ruochen; Ding, Chenming; Deng, Junyang; Guo, Yifu; Long, Shibing; Li, Ling; Li, Mengmeng
Main observation and conclusion: A few monolayers of organic semiconductors adjacent to the dielectric layer are of vital importance in organic field‐effect transistors due to their dominant role in charge transport. In this report, the 2‐nm‐thick polymer monolayers based on poly(3‐hexylthiophene) with different molecular weights ( M n ) were fabricated using dip‐coating technique. During the monolayer (solid state) formation from the solution, a disorder‐to‐order transition of polymer conformation is observed through UV‐vis absorption measurement. Meanwhile, high M n polymer monolayer generates higher crystalline fibrillar microstructure than the low M n one due to the stronger π–π intermolecular packing between polymers. More importantly, the solution aging procedure is utilized to further improve the morphology of polymer monolayers. It is obvious that after aging for 6 d, both fiber dimension and density as well as conjugation length are significantly increased under the same processing conditions in comparison to the fresh solution, and consequently the field‐effect mobilities are remarkably enhanced by 2—4 times. Note that the maximum mobility of 0.027 cm 2 ·V –1 ·s –1 is among the highest reported values for poly(3‐hexylthiophene) monolayer transistors. These results demonstrate a simple but powerful strategy for boosting the device performance of polymer monolayer transistors. Abstract : The microstructure and conjugation length of the poly(3‐hexylthiophene) monolayer are significantly improved by aging the cast solution for a few days, and the field‐effect mobilities of resultant monolayer transistors are remarkably enhanced by 2—4 times.